Hypoplastic left heart syndrome (HLHS): molecular pathogenesis and emerging drug targets for cardiac repair and regeneration. (3rd August 2021) - Bejjani, Anthony T; Wary, Neil; Gu, Mingxia
ABSTRACT: Introduction: Hypoplastic left heart syndrome (HLHS) is a severe developmental defect characterized by the underdevelopment of the left ventricle along with aortic and valvular defects. Multiple palliative surgeries are required for survival. Emerging studies have identified potential mechanisms for the disease onset, including genetic and hemodynamic causes. Genetic variants associated with HLHS include transcription factors, chromatin remodelers, structural proteins, and signaling proteins necessary for normal heart development. Nonetheless, current therapies are being tested clinically and have shown promising results at improving cardiac function in patients who have undergone palliative surgeries. Areas covered: We searched PubMed and clinicaltrials.gov to review most of the mechanistic research and clinical trials involving HLHS. This review discusses the anatomy and pathology of HLHS hearts. We highlight some of the identified genetic variants that underly the molecular pathogenesis of HLHS. Additionally, we discuss some of the emerging therapies and their limitations for HLHS. Expert opinion: While HLHS etiology is largely obscure, palliative therapies remain the most viable option for the patients. It is necessary to generate animal and stem cell models to understand the underlying genetic causes directly leading to HLHS and facilitate the use of gene-based therapies to improve cardiac development and regeneration.